OPTIMALISASI PERAN SATUAN POLISI PAMONG PRAJA PROVINSI LAMPUNG DALAM PENCEGAHAN PENYEBARAN COVID-19 DI PROVINSI LAMPUNG - Eka Suaib; Jamal Jamal; Ratna Indriati (e-JKPP, 2021)
The government, both at the central and regional levels, has an obligation to maintain order and order in society. One of the obligations of the local government is to maintain public order and order in the face of the spread of COVID-19 in Indonesia, which is carried out by Satpol PP as an extension of the regional government. The purpose of this study is to determine the values that can be applied so that the process of preventing the spread of COVID-19 carried out by the Lampung Provincial Satpol PP can run optimally so that public order and peace and protection for the people of Lampung can be implemented properly and optimally. The data collection techniques in this study are observation, interview and documentation. The number of interviews in this study were 12 people. The research method uses qualitative methods. In this study, researchers used qualitative data analysis, where the researcher went directly to the field to obtain data from the beginning to the end of the study. In general, the results of this research are as follows: 1) Satpol PP of Lampung Province has carried out activities as an effort to prevent the spread of COVID-19 in Lampung Province since the beginning of the virus spreading in this area, 2) Optimizing the role of Satpol PP in preventing the spread of COVID-19. 19 in Lampung Province is seen based on the role dimensions expressed by Santosa, namely the role as a policy, the role as a strategy, the role as a communication tool, and the role as a dispute resolution tool 3) Activities that have been carried out by the Lampung Provincial Satpol PP in maintaining security and public order in facing the spread of COVID-19 in Lampung Province has been carried out optimally.